2014
DOI: 10.1007/s13224-014-0616-2
|View full text |Cite
|
Sign up to set email alerts
|

Pregnancy in Women Aged 35 Years and Above: A Prospective Observational Study

Abstract: Pregnancy is affected by maternal age from conception till delivery. Various studies have been conducted globally to study this effect; few in developing countries. Maternal age is increasing in developing countries as well, so we have conducted this study. Method This was a prospective observational study consisting of 1,263 women booked at Jehangir hospital during a period of 2 years, fulfilling inclusion criteria and consenting for the study. They were divided into two groups; women aged 35 years and above … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

5
21
3

Year Published

2017
2017
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 22 publications
(29 citation statements)
references
References 14 publications
5
21
3
Order By: Relevance
“…The incidence of Post-partum hemorrhage is higher advance maternal age because atonicity as a result of multiparity and poor myometrial function. 13,23 In present study incidence of ante partum hemorrhage was 6.25% which is comparable to study conducted by Giri…”
Section: Discussionsupporting
confidence: 86%
See 1 more Smart Citation
“…The incidence of Post-partum hemorrhage is higher advance maternal age because atonicity as a result of multiparity and poor myometrial function. 13,23 In present study incidence of ante partum hemorrhage was 6.25% which is comparable to study conducted by Giri…”
Section: Discussionsupporting
confidence: 86%
“…Study done by Anuya A et al, 26% and Meenakashi et al,23.9% which are not comparable present study. In present studies 20 (6.94%) new born babies admitted to NICU which is lesser than studies conducted by Priyadatt D. Patel who reported 15.66% of NICU admission 7,11,13,20.…”
contrasting
confidence: 67%
“…Study by Pawde A, et al also concluded that rate of assisted conception was significantly higher among women aged 35 years and above. 5 Our study shows that pregnancy induced hypertension was slightly in higher proportion in advanced maternal age than younger maternal age (20% and 7.5% respectively) but this variation in proportions was not statistically significant as evidenced by other studies as well. 7 But many authors like Naqvi MM et al, Amarin VN et al and Ziadeh SM et al reported significantly higher proportion of pregnancy induced hypertension in elderly primigravida than non-elderly.…”
Section: Discussioncontrasting
confidence: 64%
“…2 Becoming pregnant after the age of 35 years can present a challenge because of the maternal risk factors associated with it, such as-subfertility, miscarriages, pre-eclampsia, gestational diabetes mellitus, anemia, intrauterine growth restriction, antepartum hemorrhage, higher incidence of instrumental deliveries, cesarean section, post-partum hemorrhage and fetal risk factors such as; malpresentation, multiple pregnancy, prematurity, increased NICU admissions due to increased perinatatal morbidity and mortality. [3][4][5] To summarize advance maternal age of a pregnant women is a high risk factor and such patients need to be handled by a trained person from the very early stage of pregnancy.…”
Section: Introductionmentioning
confidence: 99%
“…Studies have shown an association between AMA and gestational complications, such as gestational diabetes, gestational hypertension, C-section, preeclampsia, premature rupture of membranes, and chromosomal fetal anomalies 9,10,11,12,13,14 . However, the evidence is inconclusive regarding the association of AMA with placenta praevia (PP) and placental abruption (PA), with some studies indicating a positive association 12,14,15,16 and others showing no statistically significant association 13,17,18,19,20,21,22,23,24,25 .…”
Section: Introductionmentioning
confidence: 99%